1991
DOI: 10.2337/diacare.14.6.425
|View full text |Cite
|
Sign up to set email alerts
|

Drug Treatment of Hypertension in Patients With Diabetes Mellitus

Abstract: Patients with diabetes mellitus have an increased prevalence of hypertension and its vascular consequences, including coronary and cerebrovascular disease. Drug treatment of hypertension in diabetic subjects is fraught with potential difficulties, including the altered efficacy of medications, the increased risk of side effects, and the possibility of worsening glycemic control and increasing serum lipid levels. Despite these difficulties, treatment is an important part of reducing morbidity and mortality from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 119 publications
3
22
0
1
Order By: Relevance
“…Apresentam a vantagem de propiciar melhora da sensibilidade insulínica 122,123 . No entanto, o estudo ALLHAT 102 , comparando um alfabloqueador, a doxazosina, com o diurético clortalidona, mostrou uma maior ocorrência de eventos cardiovasculares, especialmente a insuficiência cardíaca congestiva, no grupo que usou a doxazosina.…”
Section: B 2c) (B 2c) (B 2c) (B 2c)unclassified
“…Apresentam a vantagem de propiciar melhora da sensibilidade insulínica 122,123 . No entanto, o estudo ALLHAT 102 , comparando um alfabloqueador, a doxazosina, com o diurético clortalidona, mostrou uma maior ocorrência de eventos cardiovasculares, especialmente a insuficiência cardíaca congestiva, no grupo que usou a doxazosina.…”
Section: B 2c) (B 2c) (B 2c) (B 2c)unclassified
“…13,16,17 Because of the changes in CVD risk factors in hypertensive patients receiving diuretic therapy, it was speculated that the beneficial effects of lowering blood pressure may be reduced or negated and suggested that diuretics be avoided as first-line antihypertensive drugs in patients with diabetes. 14 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, they have been recently associated with increased cardiovascular mortality [13]. The angiotensin-converting enzyme (ACE) inhibitors are probably the best current choice for hypertension in diabetes due to their well-established antihypertensive, antialbuminuric and renoprotective effects and their neutral or favorable metabolic effects [14, 15, 16, 17]. Very limited and controversial information is available on the renal effect of α-adrenergic antagonists [18, 19].…”
Section: Introductionmentioning
confidence: 99%